Suitability of commercially important Indian pomegranate (Punica granatum) cultivars for minimal processing - BHATIA, KAVITA; ASREY, RAM; VARGHESE, ELDHO; SINGH, SURINDER; KANNAUJIA, PANKAJ (The Indian Journal of Agricultural Sciences, 2015)
An experiment was conducted during 2011-2012 to select the most suitable pomegranate (Punica granatum L.) cultivars namely Mridula, Kandhari and Bhagwa for minimal processing. The effect of cultivars on quality parameters of minimally processed pomegranate arils packaged in 50 micron polypropylene bags were evaluated over 15 days during cold storage (5 ± 2 ºC and 85 ± 5% relative humidity). Aril quality was determined by measuring colour attribute (L*value), respiration rate, TSS, PLW, aril firmness, microbial growth and sensory analysis. Based on microbial limit (7 log cfu/g) and acceptance score (5), minimally processed pomegranate arils prepared from Mridula showed longer shelf-life than Bhagwa. At the end of storage (15th day), arils from Mridula cultivar showed the least browning (>L value), respiration rate, weight loss and microbial count with the highest acceptability score compared to Kandhari and Bhagwa.